Multiple disease resistance in snap bean genotypes in Kenya - Wahome, S.W.; Kimani, P.M.; Muthomi, J.W.; Narla, R.D.; Buruchara, Robin Arani (African Crop Science Society, 2011)
Snap bean (Phaseolus vulgaris L.) is an important export vegetable crop, produced mainly by small to medium scale farmers under various disease constraints. Disease resistant varieties can reduce reliance on fungicides, and enhance the capacities of smallholder farmers to meet the stringent European export requirements for allowable fungicide residues. This study was carried out to identify snap bean lines with multiple disease resistance to angular leaf spot (Phaeoisareopsis griseola), anthracnose (Collectotrichum lindemuthianum) and rust (Uromyces appendiculatus). Seven groups of snap bean populations of different generations, and 45 bush snap bean lines, including local checks, were evaluated for resistance to the three diseases at two locations in Kenya. The disease with the highest severity was rust, followed by angular leaf spot. Among the advanced lines, two bush lines (KSB 10 W and KSB 10 BR), and one climbing line (HAV 130) had consistent multiple resistance to angular leaf spot, anthracnose and rust at both locations. Nine lines and 674 single plants were selected from populations showing multiple disease resistance. Resistance in selected lines reduced angular leaf spot, anthracnose and rust severity by 17, 16 and 36%, respectively. The multiple disease resistant lines were not the highest yielders but had the highest number of pods per plant. Climbing snap bean lines had thick pods that could reduce pod quality